Risk of heavy metal pollution and product quality in rice-rape cropping system as affected by integrated fertilization with commercial organic manure and chemical fertilizers - LU Hong-juan; KONG Wen-jie; ZHANG Xiao-ling; NI Wu-zhong (浙江大学学报. 农业与生命科学版)
A field experiment was conducted to assess the impacts of integrated fertilization with commercial organic manure and chemical fertilizers on risk of heavy metal pollution and quality of agricultural products in rice-rape cropping system. Four treatments as chemical fertilizers (T1), chemical fertilizers + lower rate of organic manure (T2), chemical fertilizers + medium rate of organic manure (T3), and chemical fertilizers + high rate of organic manure (T4) were designed in the experiment. The doses of N, P2O5, and K2O of each treatment were equal, and each treatment had four replications. The results indicate that the differences of shoot biomass and grain yields of rice and rape among treatments were not significant (P>0.05). Cadmium concentration in brown rice increased with the increase in the ratio of organic manure applied. Healthy risk existed as cadmium concentration in brown rice of treatments with medium and high rate of organic manure were as high as the limit (0.2 mg·kg-1) in cereals. According to the oil content of rapeseed 35% (others are rapeseed meals) and Hygienical Standard for Feeds, cadmium and lead concentrations in rapeseed of all treatments were in the safety arrangement. It was also found that zinc and copper was obviously deficit in soil-crops system with chemical fertilizers (T1); cadmium was accumulated in the treatments applied with organic manure and lead was accumulated apparently in four treatments. It could be concluded that integrated fertilization with appropriate rate of organic manure and chemical fertilizers could not only remain the balance of zinc and copper, but also minimize the risk of heavy metal pollution in the cropping system, which can be regarded as an effective manner for the construction of sustainable agriculture.